The effects of a study of Olympism and olympic values on the attitudes and values of students in a high school classroom - Dosen, Natasa (Πανεπιστήμιο Πελοποννήσου, 2016)
The research investigated the changes in the knowledge and attitudes of high school students about the Olympic Games and the values of the Olympic sport as a result of participating in a series of lessons by the Olympic Values Education Programme (OVEP). The research has shown the impact of teaching Olympic values on students’ existing value system, their preferences toward various topics related to the Olympic sport and implementation of different activities used as teaching methods. For creating this research, a resource titled Teaching Values: an Olympic Education Toolkit (Binder, 2007), developed by the Professor Deanna Binder (2007), and produced by the International Olympic Committee for its Olympic Values Education Program was used. Moreover, case study was a proper methodology to research the effects of OVEP on participants. During the programme, which lasted for two months, students developed their interest in sport, particularly, Olympic Games. In regards with the Olympic values, they had the basis of what the values are and what is ethical. Within the research, they broadened their view of values in sport and were aspired to introspect their values and behaviour in order to try to achieve personal goals and be the best. Students expressed the biggest interest for three topics which were the part of research. Most students were interested in learning and discussing about doping. The story about Jessie Owens and Lutz Long was mentioned many times in students’ answers in questionnaires and interviews as a positive example of values. They expressed admiration and support to athletes at the Paralympic Games. The research also brought insights of using different teaching methods during the research. As a teaching method, students were more likely to participate in different activities and watch videos than just be taught by using a teaching model which exists in school system. They mostly learned through videos, presentations and group activities.
Keywords: Physical education and training - Study and teaching (Higher); Olympism; Olympic education - Curriculum; OVEP; High school students; teaching methods; Olympic Values Education Programme (OVEP); Olympic values